(untitled) (Experimental biology, 2015)
Acute poisoning by fluoroacetamide, which disturb the tricarbonic acids cicle, provoke significate change of cardiovascular and respiratory systems activity. After shot timed increase of a role humoromethobolic and sympatic activity had seen noted increase of parasimpatic influence on the heart rate variability.